2005
DOI: 10.1002/mds.20637
|View full text |Cite
|
Sign up to set email alerts
|

Recessive hyperekplexia due to a new mutation (R100H) in the GLRA1 gene

Abstract: Hyperekplexia is commonly familial and with dominant transmission. The gene involved, GLRA1, encodes the alpha1 subunit of the glycine receptor. We describe 3 affected children homozygous for a new mutation, R100H. Both parents were heterozygous carriers; while the father was healthy, the mother has periodic limb movements during sleep. This suggests that Hys-100 could exhibit incomplete penetrance, but was linked to a severe classical form of hyperekplexia in homozygous.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 12 publications
(19 reference statements)
0
6
0
Order By: Relevance
“…[1][2][3][4] Most known genetic mutations resulting in hyperekplexia involve the GLRA1 gene of the inhibitory glycine receptor. 2,[6][7][8][9][10] The inhibitory glycine receptor mediates synaptic inhibition, primarily in the brain stem and spinal cord. [11][12] That the affected members in family K6456 were found to be heterozygous for the arginine271proline mutation in GLRA1 while the unaffected members of the family were negative for the mutation strongly supports our assertion that hyperekplexia in this family is likely because of the arginine271proline mutation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] Most known genetic mutations resulting in hyperekplexia involve the GLRA1 gene of the inhibitory glycine receptor. 2,[6][7][8][9][10] The inhibitory glycine receptor mediates synaptic inhibition, primarily in the brain stem and spinal cord. [11][12] That the affected members in family K6456 were found to be heterozygous for the arginine271proline mutation in GLRA1 while the unaffected members of the family were negative for the mutation strongly supports our assertion that hyperekplexia in this family is likely because of the arginine271proline mutation.…”
Section: Discussionmentioning
confidence: 99%
“…5 The majority of these genetic mutations are alterations of the inhibitory glycine receptor alpha 1 subunit (GLRA1), located on chromosome 5q. 2,[6][7][8][9][10] This results in disruption of inhibitory synaptic responses.…”
mentioning
confidence: 99%
“…In 1993, mutations were identified in the main hyperekplexia gene, GLRA1, located on chromosome 5q33‐q35 4, 5. A point mutation in the α subunit of the glycine receptor gene GLRA1 has been identified in most pedigrees with the “major” form hyperekplexia,4, 6–10 and may be regarded the defining element of autosomal dominant ‘major’ hyperekplexia. In a few families homozygous mutations10 or compound heterozygosity8, 9 in the GLRA1 gene have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…At least one non-penetrant GLRA1 mutation has been reported. 48 There are also rare cases of hyperekplexia caused by homozygosity [49][50][51][52] or compound heterozygosity 52,53 for recessive GLRA1 mutations.…”
Section: Geneticsmentioning
confidence: 99%
“…One double-blind, placebo controlled, cross-over study that included four patients revealed that patients on clonazepam had reduced startle activity compared to vigabatrin as measured by startle to auditory stimuli. 67 Despite often dramatic response to clonazepam, 2,4,[7][8][9]16,23,25,26,29,30,[49][50][51]53,67 there are other reports that have found clonazepam to be less effective. 5,11,16,27,31,61 Saenz-Lope et al 27 found clonazepam ineffective in their three patients but had some success with the use of valproic acid and a combination of hydroxytryptophan and piracetam.…”
Section: Clonazepammentioning
confidence: 99%